The roles of metal-organic frameworks in modulating water permeability of graphene oxide-based carbon membranes - Sui, Xiao (2021)
Graphene oxide (GO) can be processed into carbon membranes with unique water permeability and molecular selectivity. Metal-organic frameworks (MOFs) have been proposed as filler materials to enhance water permeability of laminar GO-based carbon membranes. However, it remains unclear how the enhancement arises. Herein, we combined experimental and molecular simulation studies to provide critical insights into the water transport behaviors of GO/MOF composite membranes. The water permeability enhancement was found to be directly correlated to the increase in the average interlayer spacing between GO nanosheets. The simulation results indicate a slower water transport through nanochannels in MOFs than in nanochannels formed by GO nanosheets. A small amount of MOF particles only serves as a blockage in laminar GO membranes, suppressing their water permeability. In contrast, a large amount of MOF particles increases the interlayer spacing between GO nanosheets and creates very fast water transport stretches. Besides, some large gaps are formed between non-smooth MOF particles and GO nanosheets, adding supplementary water channels to deliver higher water permeability. We envision a shift in future research direction to exploit the selective adsorption capacity of MOFs other than leveraging them as fast water transport channels to realize their potential water treatment applications.